Low resistance to chytridiomycosis in direct-developing amphibians. Issue 1 (December 2017) - Mesquita, Andréa; Lambertini, Carolina; Lyra, Mariana; Malagoli, Leo; James, Timothy; Toledo, Luís; Haddad, Célio; Becker, C.
Abstract Host-generalist pathogens sporadically infect naive hosts, potentially triggering epizootics. The waterborne fungusBatrachochytrium dendrobatidis (Bd ) is linked to declines of hundreds of amphibian species with aquatic larvae. Although several population declines and extinctions attributed toBd have been reported among cryptic species undergoing direct development away from water, epidemiological studies focused on these terrestrial frogs are lacking. Our field data support that terrestrial direct-developing hosts are less exposed toBd during their ontogeny than species with aquatic larvae, and thus they might lack adaptive responses against waterborne chytrids. Using controlled laboratory experiments, we exposed wild-caught amphibian species with terrestrial and aquatic life histories toBd and found that direct developers showed more rapid increases in infection loads and experienced higher mortality rates than species with aquatic larvae. Our findings provide novel information about host responses to generalist pathogens and specifically show that our focal direct developing species have low resistance toBd infections. Finally, our results underscore that we should not ignoreBd as a potential threat to direct developing species simply because they are less exposed toBd in nature; instead future amphibian conservation plans should include efforts to safeguard hundreds of direct-developing amphibian species globally.